2010
DOI: 10.1111/j.1365-2583.2009.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of cis‐nitromethylene neonicotinoids in relation to imidacloprid binding sites in the brown planthopper, Nilaparvata lugens

Abstract: Neonicotinoid insecticides, such as imidacloprid, are selective agonists of the insect nicotinic acetylcholine receptors (nAChRs) and extensively used in areas of crop protection and animal health to control a variety of insect pest species. Here we describe that two cis-nitromethylene neonicotinoids (IPPA152002 and IPPA152004), recently synthesized in our laboratory, discriminated between the high and low affinity imidacloprid binding sites in the brown planthopper, Nilaparvata lugens, a major insect pest of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…The fact that TMX followed the trend of all the other neonicotinoids is further evidence that TMX has a bona fide nAChR binding site, as previously demonstrated . IMD is known to have two distinct binding sites in hemipteran insects: a sub‐nM‐affinity but low‐abundance site and a low‐nM‐affinity site at higher abundance . The fact that the sulfoxaflor binding site is present at relatively low abundance (in a B max range similar to that of the sub‐nM site of IMD) and is displaced at p M concentrations by IMD is highly suggestive that sulfoxaflor is selectively interacting at the high‐affinity IMD nAChR binding site.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The fact that TMX followed the trend of all the other neonicotinoids is further evidence that TMX has a bona fide nAChR binding site, as previously demonstrated . IMD is known to have two distinct binding sites in hemipteran insects: a sub‐nM‐affinity but low‐abundance site and a low‐nM‐affinity site at higher abundance . The fact that the sulfoxaflor binding site is present at relatively low abundance (in a B max range similar to that of the sub‐nM site of IMD) and is displaced at p M concentrations by IMD is highly suggestive that sulfoxaflor is selectively interacting at the high‐affinity IMD nAChR binding site.…”
Section: Discussionsupporting
confidence: 77%
“…33 IMD is known to have two distinct binding sites in hemipteran insects: a sub-nM-affinity but low-abundance site and a low-nM-affinity site at higher abundance. 8,27,36 The fact that the sulfoxaflor binding site is present at relatively low abundance (in a B max range similar to that of the sub-nM site of IMD) and is displaced at pM concentrations by IMD is highly suggestive that sulfoxaflor is selectively interacting at the high-affinity IMD nAChR binding site. This would explain why sulfoxaflor is relatively weak in [ 3 H]-IMD displacement studies, where the tracer ligand is present at a concentration in which occupancy at both sites can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the orthologs of Da3 and Db1 have been identified in neonicotinoid-resistant strains of Nilaparvata lugens (Liu et al 2005) and Myzus persicae (Bass et al 2011), respectively. While only one imidacloprid-binding site has been reported in adult D. melanogaster and other Dipteran and Lepidopteran species (Tomizawa and Casida 1997;Lind et al 1998), multiple binding sites have been reported in several Hemipteran species (Lind et al 1998;Xu et al 2010;Bass et al 2011). Unlike Hemipterans, Dipterans and Lepidopterans are holometabolous insects that undergo complete metamorphosis from larva to adult.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the activities of these compounds had no superiority over imidacloprid. But the bioassay showed that an imidacloprid resistant strain of N. lugens was with less cross-resistance to these cis-neonicotinoids, when compared to imidacloprid itself or other trans-neonicotinoids (Shao et al, 2008;Xu et al, 2010). These results implied the further structural modification to keep the cis-configuration of the eNO 2 or eCN group might give valuable results in resistance management.…”
Section: Discussionmentioning
confidence: 77%
“…The excellent activity of IPPA152201 and low cross-resistance in the imidacloprid resistant populations make it to be a potential choice. After the commercialization of the first cis-neonicotinoid (IPPA152004; Jiangsu Kwin Group Co., Ltd., China; Xu et al, 2010), it is hopeful to develop more insecticides from cis-neonicotinoids, including the nitroconjugated neonicotinoids reported in the present study.…”
Section: Discussionmentioning
confidence: 94%